The Urgency of Reformulating Just and Humane Diversion Arrangements in Juvenile Criminal Law - Krismiyarsi Krismiyarsi; Zainal Arifin (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
The diversion provisions in the Juvenile Criminal Justice System Law urgently require re-examination following as the requirement limiting diversion to offenses carrying a maximum threat under seven years in Article 7 differs from Article 2 of the SPPA Law. When evaluated against the fundamental principles of juvenile justice, this regulatory disparity creates legal inconsistency and potential injustice toward children in conflict with the law. Through philosophical, juridical, sociological, penological analyses and comparative law, this study highlights the urgency of reformulating these diversion arrangements to ensure that the best interests of the child are prioritized through equitable access to diversion at every stage of legal proceedings. Ultimately, realizing restorative and rehabilitative justice rather than retributive punishment is an imperative duty for law enforcement officers, making regulatory harmonization essential to guarantee legal certainty and judicial consistency in line with national criminal law reform. This study employs an empirical juridical research method and draws upon both primary and secondary data. The statutory requirement limiting diversion to offenses threatened with under seven years of imprisonment should be eliminated. Instead, diversion shoul Publis be established as a legal right available to every child in conflict with the law at all stages of the criminal justice process investigation, prosecution, and trial. The decision to grant diversion should be based on case-by-case guidelines evaluating the motive, the degree of harm, and the victim-offender dynamic, rather than abstract statutory penalty caps.